Maternal circulating leptin profile during pregnancy and gestational diabetes mellitus. (March 2020) - Xiao, Wan-Qing; He, Jian-Rong; Shen, Song-Ying; Lu, Jin-Hua; Kuang, Ya-Shu; Wei, Xue-Ling; Qiu, Xiu
Abstract: Aims: To evaluate the difference in maternal circulating leptin profile between pregnant women with and without gestational diabetes mellitus (GDM). Methods: This is a nested case-control study embedded in the Born in Guangzhou Cohort Study in Guangzhou Women and Children's Medical Center, with 198 GDM cases and 192 controls included. Maternal plasma leptin profile was defined as leptin concentrations measured at early (baseline) and late pregnancy, as well as a ratio of concentration at late to that at early pregnancy (R L 1 L 0 ) . General linear regression was used to assess the associations between GDM and log-transformed leptin measurements. Results: Women with GDM had a higher baseline leptin concentration and lower R L 1 L 0 compared to those without GDM. The log leptin concentration at baseline (β: 0.19, 95%CI: 0.04, 0.34) and the log R L 1 L 0 (β: −0.22, 95%CI: −0.41, −0.03) were associated with GDM status. The R L 1 L 0 decreased significantly along with the increase of 1-hour glucose and the difference between 1-hour and fasting glucose levels in both GDM and non-GDM women. Conclusions: Women with GDM had a certain profile of circulating leptin, with higher baseline concentration but less increase during pregnancy, suggesting an impaired compensatory response to increasing insulin resistance along with the progress of pregnancy.